Phase separation and fluid mixing revealed by trace element signatures in pyrite from porphyry systems. (15th July 2022) - Keith, Manuel; Haase, Karsten M.; Chivas, Allan R.; Klemd, Reiner
Abstract: Porphyry deposits host various trace elements in economic amounts, but the hydrothermal processes causing their fractionation and enrichment are still not fully understood, but vital to target the most prospective mineralisation. We present the first micro-analytical study on the trace element composition of pyrite from the Koloula Cu-Au porphyry in the young and thin (<25 km) Solomon Islands arc. A statistical evaluation of the trace element data of pyrite indicates that mineral inclusions obscure the chemical signature of the mineralisation processes. The filtered pyrite data, from which the inclusions were excluded, correlate with variations in temperature and salinity, as defined by fluid inclusions from several alteration zones. Trace element ratios in pyrite show systematic variations with fluid temperature and salinity (Co/Ni, Se/Te), phase separation (Co/Ni, Co/As) and mixing of magmatic fluids and meteoric waters (Se/Ge). The mineralisation in the potassic alteration zone was controlled by the formation of a hypersaline liquid (Co/As > 1, Co/Ni > 50) from a magma-derived fluid (Se/Ge 100) at lithostatic pressure conditions and temperatures of up to 700 °C (Se/Te > 50). This was followed by a transition to hydrostatic pressure conditions due to open-fracture continuity towards the paleo-surface, marking the onset of boiling in the chlorite-sericite to sericitic alteration zone (Co/As < 1), where minor proportions of meteoric water were involved (Se/Ge < 100). The shallowest part of the mineralisation is controlled by lower temperature (<300 °C, Se/Te < 50) vapour-rich fluids (Co/As < 1) that condensed into meteoric waters in an epithermal transition zone (Co/Ni < 50, Se/Ge < 100). Trace element systematics in pyrite from progressive alteration zones therefore preserve the time-space evolution of porphyry (-epithermal) systems in young and thin oceanic island arcs.